Analysis of the effectiveness promotion prices (cashback) with promotion prices (buy1 get1) on consumer buying decisions - Ristandi Nurcahyono; Setyo Riyanto (Faculty of Economics and Business Mulawarman University, 2021)
This study aims to find out something that influences the effectiveness in carrying out marketing strategies in the form of promotional discounts (Cashback) with promotional discounts (Buy1 Get1) on consumer purchasing power decisions. This type of research is carried out by the method of explanatory research or explanatory research with a quantitative approach. Variables used in this study include; discounted price promotions (Cashback), discounted price promotions (buy1 get1), consumer purchasing power decisions, the population of this research is the general public which is carried out randomly with a sample of 115 respondents taken using purposive sampling techniques and data collection methods using questionnaires. Analysis of the data used is descriptive analysis and path analysis.